Cochlear Implantation Outcomes in Observed Vestibular Schwannoma: A Preliminary Report. (July 2022) - Longino, Elizabeth S.; Manzoor, Nauman F.; Cass, Nathan D.; Tawfik, Kareem O.; Bennett, Marc L.; O'Malley, Matthew R.; Haynes, David S.; Perkins, Elizabeth L.
Objective: Over the last decade there has been a trend toward observation for small nongrowing vestibular schwannoma (VS). Even without tumor growth, patients commonly experience ipsilateral hearing decline, and hearing rehabilitation remains challenging. This study analyzes hearing and speech performance outcomes after cochlear implantation (CI) in observed VS. Study Design: Retrospective review. Setting: Tertiary referral center. Methods: Chart review was used to include patients with observed VS who had undergone ipsilateral CI, pre- and postimplantation audiometry, and speech performance. Tumor size pre- and postimplantation was measured with volumetric analysis. Results: Seven patients with ipsilateral VS and CI were identified. Preimplantation tumor volume was 0.11 to 1.02 cm 3 . Five subjects were implanted with a straight electrode and two with a perimodiolar electrode. The average preimplant pure tone average was 91.3 dB (range, 80-117 dB) and 61.2 dB (range, 12-118 dB) for the implanted and nonimplanted ears, respectively. In all subjects with at least 1 year of listening experience (n = 6), consonant-nucleus-consonant word scores improved at 6 months and 1 year in the CI-alone and bimodal listening conditions. AzBio scores in quiet also improved at 6 months and 1 year. Of subjects with serial pre- and postoperative magnetic resonance imaging, volumetric analysis demonstrated no tumor growth. Conclusion: Our results demonstrate that CI is a successful option for subjects with small nongrowing VS. All subjects had improved performance postimplantation. VS may continue to be observed with serial magnetic resonance imaging given increasing conditionality among CI manufacturers and ability to assess cerebellopontine angle extension despite implant artifact.